COVID-19:incidência, características clínicas e laboratoriais de pacientes hospitalizados com tromboembolismo venoso: uma experiência de três centros de assistência terciária numa cidade capital da amazônia oriental. - NEGIDIO, Adson Kevin Cunha (2023)
Background: The pandemic of COVID19 presents itself, to date, as the greatest health challenge of this century. Central physiopathology involves an infectious respiratory disease caused by SARSCoV2 capable of causing cardiovascular complications in the most severe cases, including thromboembolism. Objective: This study aims to characterize the clinical and laboratory profile of hospitalized patients with documented thrombosis/pulmonary thromboembolism during COVID19 infection. Methods: Medical records of patients hospitalized in three tertiary care medical centers in the capital city of Pará, Brazil, with deep vein thrombosis or pulmonary thromboembolism diagnosed by imaging were reviewed. Relevant epidemiological, comorbidities, and laboratory data were analyzed. Results: The incidence of venous thromboembolism was 1.3%, ranging from 0.6% to 2.25% in the different centers. Mean values for age, Creactive protein, Ddimer, body mass index, and length of stay were 46.35 years, 143.23 mg/l, 4.12 µg/ml, 27.65 kg/m², and 50.18 days, respectively. No significant correlations (pvalue <0.05) were found between any of the variables studied and the presence of thrombosis or pulmonary thromboembolism. Conclusion: There seems to be no relationship between the presence of venous thromboembolism and the presence of some prevalent endocrinemetabolic comorbidities or laboratory patterns in COVID19 infection. Individual risk factors may significantly influence the thrombotic and thromboembolic risk. Important limitations in data including the possibility of underdiagnosis and incomplete completion of medical records may confound the results. Some public health referral services need more infrastructural support. More studies should be conducted involving more accurate data.